Gerstmann–Sträussler–Scheinker syndrome with phenotypic change in dynamics and misdiagnosis of a motor neurone disease (clinical case) - Shevchuk, D. V.; Grishina, D. A.; Nuzhny, E. P.; Zakharova, M. N. (Nevrologii͡a︡, neĭropsikhiatrii͡a︡, psikhosomatika, 2024)
This article presents a clinical case of Gerstmann–Sträussler–Scheinker syndrome (GSS) – a progressive inherited prion disease with an extremely rare phenotype that changed dynamically during the course of the disease and eventually led to the misdiagnosis of a motor neurone disease. An important feature of this case is a progressive myelopathy, probably due to the deposition of prion protein plaques, with the development of symptoms of lower motor neuron involvement (muscle atrophy, areflexia, fasciculations and muscle hypotonia). Clinical, laboratory, electrophysiological and neuroradiological features of this case are presented. The final diagnosis was verified by whole-exome sequencing – a typical mutation p.P102L in the prion protein gene PRNP was identified. It is discussed whether GSS should be included in the differential diagnosis in patients with progressive motor disorders, a family history and unchanged long nerve conduction function according to electromyography.